2022
DOI: 10.1021/acs.jpcc.2c00910
|View full text |Cite
|
Sign up to set email alerts
|

Isomeric Pair of E/Z Tetraphenylethene-Cored Luminogens Showing Distinguishing Mechanoresponsive Luminescence Turn-On and Two-Color Behavior

Abstract: A pair of tetraphenylethylene (TPE)-based E/Z isomers (E-TPE2PD and Z-TPE2PD) using two dicyanovinyl groups as the electron-accepting moieties have been synthesized and separated successfully. Reversible E/Z isomerization for each isomer is achieved, in which the isomerization speed from E to Z is higher than that from Z to E. This pair of pure E/Z isomers exhibits obvious AIEE properties. Z-TPE2PD shows highly morphology-dependent solid-state photoluminescent properties, whose solid-state emission is red-shif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Based on the crystallography data, the absence and presence of π–π interactions between adjacent phenyl dicyanos were suggested to be responsible for the distinct solid MCL properties of these isomers. 72 Further work revealed that two polymorphous meso -dicyanovinyl-substituted TPEs also followed the above rule ( 2-12 , 2-13 , Fig. 6b), where the compounds showed ultrahigh-contrast MCL (Δ λ em = 141 nm).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Based on the crystallography data, the absence and presence of π–π interactions between adjacent phenyl dicyanos were suggested to be responsible for the distinct solid MCL properties of these isomers. 72 Further work revealed that two polymorphous meso -dicyanovinyl-substituted TPEs also followed the above rule ( 2-12 , 2-13 , Fig. 6b), where the compounds showed ultrahigh-contrast MCL (Δ λ em = 141 nm).…”
Section: Discussionmentioning
confidence: 78%
“…Nevertheless, the photoinduced cis – trans isomerism is more considerable based on many more demonstrations, which could also produce photochromism. 72 In the report of Sun's group, a simple cyanostilbene derivative also displays a complex solvatochromism, acidichromism, mechanochromism, and photochromism ( 2-24 ). This multiple stimuli response benefits from an additional dimethylamino group to afford enhanced CT specialty and protonation site.…”
Section: Discussionmentioning
confidence: 99%
“…The dicyanovinyl (DCV) group, owning to its strong electron-withdrawing property and good planarity, was frequently used in building red-emitting emitters. So far, a variety of donor–acceptor luminogens based on TPE and DCV have been exploited. The DCV units of these compounds were mostly located in the para -substituted benzene ring to better represent the intramolecular charge transfer (ICT) effect. Our group recently reported a pair of isomers whose single-crystal structures showed that one para -substituted DCV group and its connected benzene ring were nearly coplanar with the assistance of intramolecular hydrogen bonding .…”
Section: Introductionmentioning
confidence: 99%
“…So far, a variety of donor–acceptor luminogens based on TPE and DCV have been exploited. The DCV units of these compounds were mostly located in the para -substituted benzene ring to better represent the intramolecular charge transfer (ICT) effect. Our group recently reported a pair of isomers whose single-crystal structures showed that one para -substituted DCV group and its connected benzene ring were nearly coplanar with the assistance of intramolecular hydrogen bonding . As far as we know, all of these reported DCV-modified TPE luminophores exhibited only one crystalline state and moderate contrasts of MRL performance. As an extensive study in this area, we tried to implant herein two rigid DCV units into one benzene ring of TPE at two meso -positions ( TPE- m -2DCV ) for the first time in order to avoid the intramolecular steric hindrance impacts between two DCV groups themselves ( ortho ) as well as those between DCV groups and their adjacent aromatic rings ( para ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation